2012
DOI: 10.1089/gtmb.2012.0244
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and the Role of Dopamine D2 Receptor and Cannabinoid Receptor-1 Gene Polymorphisms

Abstract: No significant difference was found between genotypes and alleles of DRD2 Taq1A and DRD2 Taq1B polymorphism in patients and controls, while the CNR1 receptor 1359G/A polymorphism and the presence of the A allele may be one risk factor for susceptibility to obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The rs1049353 mutant allele was associated with lower BMI in six European populations and with decreased fat mass in a Danish population (n = 783) . Conversely, homozygosity for the rs1049353 mutant allele was associated with higher WHR and WC in obese men ( P < 0.01; n = 1064) and with increased childhood obesity in a European population ( P = 0.01; n = 200) . The majority of associations with rs1049353 were neutral (90%) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The rs1049353 mutant allele was associated with lower BMI in six European populations and with decreased fat mass in a Danish population (n = 783) . Conversely, homozygosity for the rs1049353 mutant allele was associated with higher WHR and WC in obese men ( P < 0.01; n = 1064) and with increased childhood obesity in a European population ( P = 0.01; n = 200) . The majority of associations with rs1049353 were neutral (90%) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study in Turkey, Araz et al . found that 1359G/A polymorphism in cannabinoid receptor‐1 ( CNR1 ) genes was associated with childhood obesity . In a recent genetic association analysis of 30 genes related to obesity in a European American population, rs912127 in HTR2A was associated with obesity .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in two studies with Turkish obese children the variant allele frequency was 51.0% in one 57 and only 20.0% in the other research. 58 In the Netherlands, the A1 allele frequency was 18.3% in obese children 59 and in NorthAmerican studies with obese children, it ranged from 17.0% 60 to 38.5%. 61 In a Brazilian study with obese and normal weight (controls) children, the A1 allele frequencies were 34.5% and 23.0%, respectively, and a statistically significant association between the A1 allele and obesity was verified.…”
Section: Drd2 Taqia Polymorphismmentioning
confidence: 98%